A construção de um campo artístico: a atuação docente de Pedro Américo na Academia Imperial de Belas Artes - Sousa, Wellington Oliveira de (2017)
The dissertation discusses the teaching performance of Pedro Américo de Figueiredo e Mello, artist of the second half of the XIX, in one of the official institutions the Empire, the Imperial Academy of Fine Arts. The Academy, together with the IHGB, Pedro II College, among other institutions, was part of a broad political project that emanated from the Court, responsible for the elaboration of a National Identity and the construction of the idea of a Nation. Beginning with the Pedreira Reform (1855), Porto Alegre as one of the idealizers, AIBA sought to consolidate itself as a major institution of the arts in the Empire, as well as to elaborate a Brazilian school. For this project, the institution sought a particular teaching profile, formed mainly by artists formed by it, endowed with a habitus, which for Bourdieu (1983) is a set of knowledges and dispositions that are incorporated by the subjects in a process of socialization. Pedro Americo, a recent graduate of the AIBA and former Emperor's pensioner in Europe, in 1864, fit this desired profile, for he was imbued with the ideals of the 1855 Reform project, endowing the capacity in continuity with his objectives: an artistic field. The study's scope extends from the contest of Pedro Américo to the Imperial Academy in 1864, to the time that the painter was absent from the institution in the 1880s. The research is based on a vast set of sources, formed by the laws and decrees of the imperial period, the Carioca newspaper Correio Mercantil, in the Discourses (1888) by Pedro Américo. And in the collection of AIBA, which is D. João VI Museum, in Rio de Janeiro, which has correspondences, official documents important for understanding the functioning of said institution.